“Gender Bias in Guest Perceptions of Female Hotel Staff” - Ms. Mubeen Amir Shaikh; Dr. Pradyuman Singh Rathore (Revista Electronica de Veterinaria, 2024)
Gender bias is a persistent issue across industries, and the hospitality sector is no exception. This study explores the phenomenon of gender bias in guest perceptions of female hotel staff, focusing on how stereotypes and societal norms influence guest interactions, expectations, and satisfaction.  This study examines the challenges faced by female staff in various hotel departments, including front office, housekeeping, food and beverage service, and management roles.The findings reveal that guests often perceive female employees through a lens shaped by traditional gender roles, associating them with nurturing and service-oriented tasks while underestimating their leadership and technical capabilities. These biases impact not only the experiences of female staff but also their career progression and job satisfaction.Furthermore, it provides actionable recommendations for hospitality organizations to foster a more equitable and inclusive environment, such as implementing gender sensitivity training for guests and staff, promoting female leaders, and challenging stereotypes through marketing strategies.This study underscores the need for the hospitality industry to address gender bias proactively, ensuring a fair and empowering workplace for female employees while enhancing the guest experience through diversity and inclusion.